Razmerje med pravom in politiko prek zasebne lastnine - Lukšič, Igor (Teorija in praksa, 2024)
The article builds on the thesis that the mode of production of people’s lives is the key to understanding the law–politics relationship. Capitalism is driven by the logic of capital concentration, which is only possible with a continuous process of privatisation, i.e., the converting of all individualisable things into private property. The author builds this line of argument while presenting ideas from Aquivinas to Locke and Smith. Aquinas already perceives the power of bourgeois politics and the emerging mode of production, which with More makes an attempt at an alternative with the establishment of common ownership, whereas with Locke and Smith the victory of capitalism is conceptually closed in concepts that still apply today. Law and politics are at the service of the accelerated concentration of capital and accordingly develop solutions that are line with the reproduction of this world system.
Keywords: Adam Smith; capitalism; concentration of capital; feudalism; fevdalizem; John Locke; kapitalizem; koncentracija kapitala; law; Locke, John; mode of production od the people; način produkcije ljudi; politics; politika; Politika in vladanje; pravo; Pravo in politika; private property; privatisation; privatna lastnina; Smith, Adam; Tomaž Akvinski